Financial Innovation and Sustainable Development in Selected Countries in West Africa - Folorunsho M. Ajide (Journal of Entrepreneurship, Management and Innovation)

(untitled)
Financial innovation has given a new trend to modern financial system and its importance has been widely recognized. This study investigated the effect of financial innovation augmented with bank competition on sustainable development in eight West African countries. Data were sourced from World Bank development indicators from years 2000-2013. We used two proxies of competitions, two proxies of financial innovations and regressed them on a growth indicator as well as development indicator with other control variables. Using panel data estimations, our results confirmed that an increase in banking efficiency driven by competition and financial innovation would improve economic growth and development. While the two proxies of competition were significant, the financial innovations were not significant; one displayed a negative, while the other exhibited a positive relationship with development. These results revealed the differential effects of different financial innovations adopted in the financial system. That is, the growth effect of financial innovation is sensitive to the choice of proxy. A reduction in demand for money caused by financial innovations could deter economic growth and development. This is because individuals would move away from more liquid assets to less liquid assets. On the other hand, financial innovations could potentially lead to an increase in money demand if payment systems improve and individual’s demand for more liquid assets is channeled to productive sectors. We therefore concluded that policies which would drive competition and efficiency in the banking industry as well as financial innovation should be introduced to ensure effective functioning of the financial system.